Manipulation the behavior of supramolecular hydrogels of α-cyclodextrin/star-like block copolymer/carbon-based nanomaterials. (6th March 2015) - Shen, Jinglin; Xin, Xia; Zhang, Yongjie; Song, Lifei; Wang, Lin; Tang, Weiyue; Ren, Yingjie
Highlights: α-Cyclodextrin/star-like block copolymer AE73 hydrogels were prepared. Graphene and graphene oxide were successfully incorporated into the α-CD/AE73 hydrogel. Graphene (hydrophobic) and graphene oxide (hydrophilic) have different effects on the formation of hydrogels. The incorporation of graphene and graphene oxide impart versatile functionalities for hydrogels. Abstract: A new supramolecular hydrogel self-assembled between α-cyclodextrin (α-CD) and a star-like block copolymer AE73 was prepared. The cooperation effect of complexation of poly-(ethylene oxide) (PEO) segments with α-CD and the hydrophobic interaction between poly-(propylene oxide) (PPO) blocks resulted in the formation of the supramolecular hydrogel with a strong macromolecular network. Then two kinds of carbon materials (graphene and graphene oxide) were successfully incorporated into the above α-CD/AE73 hydrogel to further enhance the mechanical properties. The native hydrogel, as well as hybrid hydrogels, have been thoroughly characterized by using various microscopic techniques, including transmission electron microscopy (TEM), field emission scanning electron microscopy (FE-SEM), Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), thermogravimetric analysis (TGA). Our main purpose is to ascertain whether the properties of the obtained gels depend on these architectures. Interestingly, the phase behavior, the morphology and the mechanical strength of the native hydrogel can be successfully modulated by incorporating graphene and graphene oxide. Taking into account that both PEO/PPO copolymers and α-CD seem to be biocompatible, these gels can be promising for biomedical applications.